2017
DOI: 10.2134/cftm2016.10.0068
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Droplet Size of Foliar‐Applied Nitrogen on Grain Protein Content of Hard Red Winter Wheat

Abstract: Core Ideas Application of foliar‐applied N postanthesis increased grain protein concentration (GPC). Increasing GPC of wheat may allow producers to avoid costly discounts and obtain premiums. No differences were observed in performance among three common agronomic droplet sizes. Improvement in GPC is related to the amount of N measured in the flag leaf after foliar N application. Larger increases in GPC are observed when grain yields are at or above average. Effectively increasing the grain protein concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Another study reported that contents of gliadins, glutenins, albumins/globulins and peptides for celiac disease epitopes are affected more by the year of cultivation of the wheat cultivars than by the wheat cultivars themselves [26,29]. Similarly, classically determined kernel raw protein appears to be influenced largely by environmental factors such as nitrogen fertilization, weather conditions and soil types [2,4]. In line with these findings, the total protein content determined by NIRS technology in our dataset had a heritability of 0.65, while the sedimentation volume or the thousand kernel weight and hectoliter weight had heritability close to 0.9 [37].…”
Section: Complex Interaction Between Proteins Cultivars and Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study reported that contents of gliadins, glutenins, albumins/globulins and peptides for celiac disease epitopes are affected more by the year of cultivation of the wheat cultivars than by the wheat cultivars themselves [26,29]. Similarly, classically determined kernel raw protein appears to be influenced largely by environmental factors such as nitrogen fertilization, weather conditions and soil types [2,4]. In line with these findings, the total protein content determined by NIRS technology in our dataset had a heritability of 0.65, while the sedimentation volume or the thousand kernel weight and hectoliter weight had heritability close to 0.9 [37].…”
Section: Complex Interaction Between Proteins Cultivars and Environmentmentioning
confidence: 99%
“…aestivum) is grown globally in over 120 countries, covering 16% of the cultivated land area, and is therefore a key source of carbohydrates and proteins for growing populations (https://www.wheatinitiative.org/, accessed on 3 October 2020). Protein contents in wheat grains depend on the chosen cultivar due to significant genetic variations [1], to contrasting fertilizer management and to environmental factors such as soil, rainfall and temperature, all affecting the nutrients uptake [2][3][4]. Furthermore, the grain protein content is negatively correlated with grain yield and grain starch content [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach to improve the fertilizer-NUE is foliar fertilization, where liquid Nfertilizer is sprayed directly onto the leaves, thereby bypassing the soil from which N is easily leached or volatilized [23]. Foliar N-fertilization (FNf) also offers greater possibilities to match plant demand and N supply during the growing season, which might further improve the fertilizer-NUE [24,25]. Foliar fertilization with various N sources may, however, cause leaf scorching [22,23,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, N application at late growth stages has less influence on grain yield but better effects on grain protein accumulation [16,17]. As N is allocated faster to grains through leaf application [18], the practice of applying N solutions to the canopy is commonly used only late in the growing season, particularly at anthesis [19][20][21] or early milk [22], with the aim of improving flour quality and the bread-making properties [23].…”
Section: Introductionmentioning
confidence: 99%